Description of Cervical Cancer Case at Dr. Pirngadi Hospital Medan - Hrp , Fitri Aidani Ulfa (SEAN Institute, 2024)
Cervical cancer is one of the diseases that causes broad psychosocial impacts, especially for patients and their families. According to Racmadahniar (2005), in 2000 about 80% of cervical cancer. The lack of public knowledge about cervical cancer is caused by things such as lack of awareness and willingness of the public to check themselves or consider doing an examination requires expensive costs. The cervix is part of the uterus. The type of research used in this study is to describe how cervical cancer cases. The data collection technique in this study is using secondary data. From the results of research cases of cervical cancer based on age with the age of >35 years as many as 41 people (100%). Cervical cancer cases are based on the majority of education with high school education as many as 17 people (41.47%). Cervical cancer cases based on the majority of occupations with IRT/self-employed jobs as many as 18 people (72%). Cervical cancer cases are based on majority parity with parity 3-5 as many as 41 people (100%). Cervical cancer cases are based on the majority of treatment with therapeutic treatment as many as 35 people (85.37%). To increase the knowledge of every adult (fertile) woman about cervical cancer.